Records of Radio Aurora at Syowa Station, Antarctica from April 1970 to February 1971 - シロ, イサオ; サカモト, トシロウ; SHIRO, Isao; SAKAMOTO, Toshirou (National Institute of Polar Research, 1972)
P(論文) departmental bulletin paper